Integrated analysis of oral rinse-derived and plasma circulating tumour DNA for mutation profiling and outcome prediction with oral squamous cell carcinoma - Zhuo Chen; Lihuang Chen; Shuaize Li; Peng Xia; Alfred King-yin Lam; Jie Qiao; Yi Liu; Bin Qiao (npj Precision Oncology)
Abstract This study evaluates the potential of oral rinse-derived and plasma circulating tumour DNA (ctDNA) in HPV-negative oral squamous cell carcinoma (OSCC), where early recurrence occurs in a significant proportion of patients, contributing to poor prognosis. Analysis of paired tissue, oral rinse, and plasma samples from 123 patients revealed ctDNA detection rates of 94.3% in oral rinse and 80.5% in plasma samples. Combined testing improved mutation detection sensitivity to 48.6%. A machine learning model integrating seven mutated genes (TP53, TERT, IKZF1, EP300, MYC, EGFR, PIK3CA) and clinical factors demonstrated robust prediction of recurrence (validation AUC: 0.854) and survival outcomes. Integration of pretreatment plasma ctDNA status further enhanced predictive performance. In longitudinal analysis, ctDNA detected recurrence approximately four months before clinical manifestation. These findings suggest that integrated ctDNA analysis offers improved mutation profiling and outcome prediction, potentially enabling earlier interventions in OSCC.